Gender Audit as Basis in Developing Modules for GAD Focal Persons in Mati, Davao Oriental, Philippines - Villegas Jhonnel P.; Bauyot Mary Fil M.; Sacro Jeralyn H.; Siarot Leorisyl D. (Discourse and Communication for Sustainable Education, 2023)
Many countries across the globe, including the Philippines, have implemented Gender and Development (GAD) policies to reduce gender biases and promote equality. However, mainstreaming efforts have been challenging due to the scarce availability of learning resources in the local context. This study is an initiative to provide the GAD Focal Point System (GFPS) in the Department of Education – City of Mati with a primary reference in training their GAD Focal Persons on Gender Sensitivity, GAD Planning, and Budgeting (GPB). The coverage is based on their learning needs and gaps determined through participatory strategies involving the school administrators, teachers, students, and parents. Also, the results of the gender audit using the Gender Mainstreaming Evaluation Framework (GMEF) are used as a baseline in module development. The framework presents strategic directions that agencies need to follow to advance across stages. It was found that Mati’s primary and secondary schools are in the initial stages of gender mainstreaming. As such, GAD’s basic concepts and definitions are introduced, along with various forms of gender-based violence and the appropriate mechanisms to address them aptly. The essential steps in planning and budgeting are also detailed, providing an active experience among the participants. It is imperative to sustain GAD capacity-building initiatives to catalyze a more directed and engaged policy framework.